Novel opportunity of treatment for psycho-cardiologic disease by gut microbiome - Lai, Yurui; Fang, Chenli; Jiang, Yuang; Yang, Chengying; Zhou, Qiao; Cai, Yihua; Wei, Yan; Fan, Xinrong (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular disease (CVD) patients combined with depression, anxiety, and other psychiatric disorders are becoming a common occurrence. There are many comorbid mechanisms, and CVD patients with psychiatric disorders have poor prognosis. Several studies have shown that dysbiosis and metabolite alterations in the gut were major risk factors for CVD and psychosomatic disorders. This review aims to summarize the mechanisms of gut microbiota and its metabolites in psycho-cardiologic disease, and the therapeutic effects of gut microbiota interventions. It is very useful to propose a new direction for the treatment of psycho-cardiologic disease.